2020
DOI: 10.1111/nhs.12729
|View full text |Cite
|
Sign up to set email alerts
|

Stress and mood of adults with moyamoya disease: A cross‐sectional study

Abstract: Moyamoya disease in adults is a chronic, progressive disorder characterized by fine collateral vessel networks in the brain. The disorder can lead to negative mood and stress, which, left unresolved, may increase adverse health outcomes. We conducted a cross‐sectional survey to examine stress and mood of adults with moyamoya disease. Participants were recruited at a university hospital in Seoul, Korea. Data were collected through questionnaires and review of participants' electronic medical records. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…This finding is in accordance with the results of a study on the Dutch version of the PsyMate, which presented sensitivity to the change of mood over time and applicability for patients in an ambulatory mental health setting in the Netherlands [ 25 ]. The poor ICCs may reflect the dynamics of affect fluctuating and changing over time [ 41 ] and the variability in the anxious and depressive mood of patients with MMD [ 7 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with the results of a study on the Dutch version of the PsyMate, which presented sensitivity to the change of mood over time and applicability for patients in an ambulatory mental health setting in the Netherlands [ 25 ]. The poor ICCs may reflect the dynamics of affect fluctuating and changing over time [ 41 ] and the variability in the anxious and depressive mood of patients with MMD [ 7 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Finally, MMD may present with neuropsychiatric symptoms such as mood change, anxiety, and depression. 10 …”
Section: Natural History and Neuropsychiatric Manifestations Of Moyam...mentioning
confidence: 99%
“…However, after the initial period of cognitive decline, MMD patients’ cognitive function remains relatively stable long-term regardless of their stroke history. 11 A cross-sectional study 10 found that Korean MMD patients had higher levels of anxiety and depression than Korean and Dutch patients who previously had strokes and German patients with unruptured aneurysms. MMD patients within one year of diagnosis experience greater depression than patients diagnosed for one year or more.…”
Section: Neuropsychiatric Manifestations Of Moyamoya Diseasementioning
confidence: 99%
“…A systematic review [14] showed that the incidence rate of cognitive impairment in MMD was approximately 30%, with moderate to severe disturbance across varied cognitive domains. Although psychiatric changes are usually not onset symptoms, recent cross-sectional studies [15,16] found that depression, anxiety, and posttraumatic stress syndrome were common complications in MMD survivors and were correlated with neurological impairment [15]. Hippocampus atrophy is regarded as an imaging hallmark of dementia and is seen in a variety of neurodegenerative diseases and poststroke dementia patients [17].…”
Section: Introductionmentioning
confidence: 99%